442 OVERWEIGHT AND TAKOTSUBO SYNDROME: SHORT- AND LONG-TERM OUTCOME. RESULTS FROM A MULTICENTER PROSPECTIVE REGISTRY. (15th December 2022) - Ragnatela, Ilaria; Santoro, Francesco; Vitale, Enrica; Cetera, Rosa; Mallardi, Adriana; Leopizzi, Alessandra; Matera, Annalisa; Correale, Michele; Iacoviello, Massimo; Brunetti, Natale Daniele
Abstract: Background: Takotsubo Syndrome (TTS) is a clinical condition characterized by an acute transient heart failure with reversible ventricular motion abnormalities. Obesity is related with an increased oxidative stress, which is one of the postulated mechanism of TTS. Aim of the study: To investigate the association between Body Mass Index (BMI) and in-hospital and long-term follow-up events among patients with TTS. Methods: 178 consecutive patients with TTS at admission were enrolled in a multicenter international registry. According to BMI, patients were divided into two groups: normal-weight (BMI 18.5-25 Kg/m 2, N=70) and over-weight (BMI ≥ 25 Kg/m 2, N=78). Medical history, clinical data, echocardiographic parameters and in-hospital and long-term follow-up events of all patients were evaluated. Results: Mean body mass index was 26±5 Kg/m 2 . There were no significant differences between over- and normal- weight patients in terms of sex, age and cardiovascular risk factors (diabetes, dyslipidaemia, smoking habit) except for arterial hypertension (85% vs 67%, p=0.01). When evaluating non cardiovascular comorbidities, overweight patients had a higher prevalence of chronic pulmonary diseases (38% vs 20% p=0.018). During hospitalization no differences in terms of admission LVEF and hospital length of stay were found; however, overweight patients had higher rates of in-hospital complications (51 vs 27%, p=0.004). At follow-up, overweight patients had higher rate of MACE (44% vs 27%, p=0.03), one-year (32% vs 15%, p=0.02) and long-term mortality (37% vs 24%, log rank p=0.01), but no differences in terms of rehospitalizations and TTS recurrence. Conclusion: Overweight in TTS is associated with higher rates of in-hospital events and long-term mortality and MACE.